Catalytic Ionic‐Liquid Membranes: The Convergence of Ionic‐Liquid Catalysis and Ionic‐Liquid Membrane Separation Technologies. Issue 1 (22nd September 2017) - Izák, Pavel; Bobbink, Felix D.; Hulla, Martin; Klepic, Martina; Friess, Karel; Hovorka, Štěpán; Dyson, Paul J.
Abstract: Membrane technologies enable the facile separation of complex mixtures of gases, vapours, liquids and/or solids under mild conditions. Simultaneous chemical transformations can also be achieved in membranes by using catalytically active membrane materials or embedded catalysts, in so‐called membrane reactors. A particular class of membranes containing or composed of ionic liquids (ILs) or polymeric ionic liquids (pILs) have recently emerged. These membranes often exhibit superior transport and separation properties to those of classical polymeric membranes. ILs and pILs have also been extensively studied as separation solvents, catalysts and co‐catalysts in similar applications for which membranes are employed. In this review, after introducing ILs and their applications in catalysis, catalytic membranes and recent advances in membrane separation processes based on ILs are described. Finally, the nascent concept of catalytic IL membranes is highlighted, in which catalytically active ILs/pILs are incorporated into membrane technologies to act as a catalytic separation layer. Abstract : Barriers leading to progress : The convergence of ionic‐liquid catalysis and ionic‐liquid membrane separation technologies is leading towards the development of catalytically active separation layers, at which valuable chemical transformations are performed simultaneously with product purification through the ionic membrane material (see figure).